Analytical approach for a heat transfer process through nanofluid over an irregular porous radially moving sheet by employing KKL correlation with magnetic and radiation effects: applications to thermal system - Raizah, Zehba; Khan, Umair; Zaib, Aurang; Ishak, Anuar; Waini, Iskandar; Galal, Ahmed M. (MDPI, 2022)
The aluminum nanoparticle is adequate for power grid wiring, such as the distribution of local power and the transmission of aerial power lines, because of its higher conductivity. This nanoparticle is also one of the most commonly used materials in applications in the electrical field. Thus, in this study, a radiative axisymmetric flow of Casson fluid, induced by water-based Al2O3 nanofluid by using the Koo–Kleinstreuer–Li (KKL) correlation, is investigated. The impact of the magnetic field is also taken into account. KKL correlation is utilized to compute the thermal conductivity and effective viscosity. Analytical double solutions are presented for the considered axisymmetric flow model after implementing the similarity technique to transmute the leading equations into ordinary differential equations. The obtained analytic forms were used to examine and discuss the velocity profile, the temperature distribution, reduced heat transfer, and coefficient of reduced skin friction. The analytic solutions indicate that the velocity profile decreases in the branch of the first solution and uplifts in the branch of the second solution due to the presence of an aluminum particle, whereas the dimensionless temperature enhances in both solutions. In addition, the Casson parameter increases the friction factor, as well as the heat transport rate.